THE IMPLEMENTATION OF TEACHING ENGLISH (CASE STUDY AT ISLAMIC BOARDING SCHOOL) - Rofi'i, Agus (Universitas Wiralodra, 2018)
Introducing English earlier starts from elementary school is a bright idea, because Learning at young age will be more quickly and effectively than at adult because the child brain is particularly adaptable to language acquisition up to puberty. The writer has objectives concerning the teaching learning process, among other things are: the instructional material, the instructional media, method and technique used, and the students? achievement. This research is qualitative research design, and the subjects of the research are the headmaster, the English teacher, and students. The result of the research has been shown in the research finding and has been discussed that (1) the instructional materials (2) the instructional media is important instrument to be used and interesting for students in teaching learning process; (3) the method used are direct method, total physical respond and grammar translation method, while the technique are songs, and dialogue; (4) the students? achievement score is taken from the first semester examination. Finally, the conclusion of this research is that in holding the English as local content, while the material given, teaching media, method and technique used have been suitable with the theory although those should be improved again.